Teaching Literature through Multimedia: A Comparison of Maitree Express with the Novel t he Shadow Lines (Proceeding of the International Conference on Arts and Humanities, 2020)
While most of the world today, is struggling with the various problems of immigration, terrorism, racism …a part of it is trying very hard to reconcile with the inherent differences betweenhuman evolution. With the proximity and commonality that digital and media resources have facilitated, the world has shrunk and become accessible from any part. The last few decades have seen a paradigm shift in the methods of imparting education and use of technology to make learning more tangible. In this transitional phase the major shift in education has been, to try and use these facilities for better understanding of different cultures, artwork, music, literature and science. My paper explores the possibility of making use of the multimedia technology in discovering ways and means to bring the learners closer to the text they read. I have taken the example of the postcolonial diasporic author Amitav Ghosh to extend my findings and opinions to the audience. Teaching the works of writers such as Amitav Ghosh and many others like Salman Rushdie, Jhumpa Lahiri, Naipaul, to name a few, has become more achievable and enjoyable because the use of media simulates a quasi-environment rendering the writer’s perspective and image to the reader. Not just the character growth but the entire backdrops of many of their works are built up to reflect a struggle during transition from the discrete to the global; and, what could be better than to address their works through visual and auditory media, that can transform the written word into a relatable experience? The works of such writers as Ghosh, attempt to infuse the reader with thoughts of an emerging colonial people who, through the trauma and joy of living in hardship, have discovered the power of expression in social media and pop culture. Movies like, Salaam Bombay, Namaste London , Swades, Monsoon Wedding etc. are some movies that rewrite the past and reflect the present. Such fiction and movies are now poised to slowly start influencing the global perspectives. For generations the effects of colonization like the stereotyping of the Indian masculanity as being lazy, indulgent and lusty or that of Indian culture as that of pagans with nothing to takeaway, would be endured by the people of the colonized nations. Using multimedia for teaching allows a teacher to establish an immediate connect with her learners. Alluding to the visuals, movie depiction of a novel or a documentary, can bring alive the sentiments the writer has juggled within the narrative, especially if it is as subtle as the identity crisis!In this context my paper argues that since the learners are often unaware of the cultural context in which a story was woven, a movie depiction can bring them closer to the real life experience and increase the sensitisation of the theme. I make a comparison of The Shadow Lines, the much appreciated and acclaimed novel of the writer Amitav Ghosh, with the BBC documentary Frontier Railways, to assert this hypothesis.
Keywords: Nostalgia; Identity; multimedia